PERSEPSI MAHASISWA TERHADAP PROFESIONALITAS DOSEN (Studi di IAIN Padangsidimpuan) - DALIMUNTHE, IRWAN SALEH; LUBIS, AGUS SALIM (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The research aims to describe of perception toprofesional lecture IAIN Padangsidimpuanconcicst of: (1) pedagogic competence, (2) personality competence, (3) professional competence, (4) social competence. Kind of this research is survey research of students IAIN Padangsidimpuan. The subject of research are students of IAIN Padangsidimpuan that is listed as active student on academic year 2013-2104. The students in III (third), V(fifth), and VII (seventh) semester. The population totally 2695 students, and for the research sample totally 270 students.Instrument of collecting data doneby use research questioner. Data is collected analysed by descriftive analysis,althoughcentral dispasing or with presentaceThe result researchshow that: (1) students perception of IAIN Padangsidimpuan to pedagogic competence 19,6% very good, 67,1% good, and 13,3% enough, (2) students perception of IAIN Padangsidimpuan to personality competence 79,1% very good, and 20,9% good, (3) students perception of IAIN Padangsidimpuan to profesional competence 72% very good, and 28% good, and (4) students perception of IAIN Padangsidimpuan to social competence 75,1% very good and 24,9% good.